Immunochemical characterization of cross-reactivity of pneumococcal group 9 capsular polysaccharide types 9N, 9A, 9L, and 9V. - Szu, S (Infect Immun, 1981)
The chemical composition and immunochemical characterization of the four cross-reactive pneumococcal capsular polysaccharides within group 9 (types 9N, 9A, 9L, and 9V) were investigated. Their serological reactions were studied by using unabsorbed antisera prepared by immunizing rabbits with pneumococci of each of the four group 9 capsular polysaccharide types. Type 9A antiserum showed the most extensive cross-reactions with the four group 9 polysaccharides. Absorption with type 9N, 9L, or 9V polysaccharide removed 63, 96, or 87%, respectively, of the heterologous antibodies from the type 9A antiserum. All four of the group 9 polysaccharides contained glucose, N-acetylmannosamine, and glucuronic acid. In addition, types 9N and 9L had N-acetylglucosamine, and types 9A, 9L, and 9V contained galactose. Reduction of the uronic acid residues of the type 9 polysaccharides removed most of their homologous and much of their heterologous reactivities, indicating an important role for the uronic acid component in their antigenicity. The four group 9 polysaccharide preparations had comparable molecular sizes and only traces of protein and nucleic acid. Further studies to evaluate the most protective type among the group 9 strains to be included in the current pneumococcal vaccine are discussed. IMAGES: